2017
DOI: 10.1001/jamaoncol.2017.0257
|View full text |Cite
|
Sign up to set email alerts
|

FLT3 Mutation Testing in Acute Myeloid Leukemia

Abstract: A previously healthy man in his 50s presented with headache and blurry vision. Laboratory data are summarized in the Table . He was diagnosed with acute myeloid leukemia (AML) complicated by leukostasis. Bone marrow karyotyping revealed a normal karyotype; 46 XX [20]. Multigene polymerase chain reaction (PCR) testing of the bone marrow identified a 44-base pair (bp) internal tandem duplication in the FLT3 gene (OMIM 136351), with an allelic ratio of 0.57 (range, 0.01 to >100). No other mutations on the panel (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Since then, several methods have been developed or adapted for identifying mutations and aberrant karyotypes (Table 1) [ [45][46][47][48][49][50][51]. These methods vary in their sensitivity, turnaround time, and development stage [52]. Some methods have been used in the clinic for >10 years, while others are still being validated.…”
Section: Methods For Testing Flt3mentioning
confidence: 99%
“…Since then, several methods have been developed or adapted for identifying mutations and aberrant karyotypes (Table 1) [ [45][46][47][48][49][50][51]. These methods vary in their sensitivity, turnaround time, and development stage [52]. Some methods have been used in the clinic for >10 years, while others are still being validated.…”
Section: Methods For Testing Flt3mentioning
confidence: 99%
“…With only 10% of leukemia patients and 25% of AML patients presenting with mutations in FLT3, biomarkers are becoming increasingly useful to connect patients to the correct therapy [ 32 ]. As one example, the companion diagnostic LeukoStrat CDx FLT3 mutation assay, was FDA-approved alongside midostaurin in April 2017, and the Phase III trial showed an improved OS rate of 23% [ 33 ].…”
Section: Classic Biomarker-based Approaches For Precision Diagnosticsmentioning
confidence: 99%